Answer:
x=0
y=6
Step-by-step explanation:
Two equations with two unknowns can be solved. Use the three steps given below.
In general you can save time if you use the simplest expression for step 1. You can choose either expression to start with x =.. or you can rewrite it, so it starts with y =...
FOLLOW THESE STEPS:
1. Rewrite the first expression so it starts with y =...
2. Then use that expression and substitute it in the other expression, to find the value for x.
3. Use that value found in step 2. and substitute it in the rewritten expssion you created in step 1. Solve this last expression and you'll get the value for y.
Step 1.
-6y + 11x = -36
-6y = -11x -36
multiply left and right of the = sign by -1
6y = 11x + 36
divide left and right of the = sign by 6
y = 11x/6 + 36/6
y = 11/6x + 6
Step 2.
-4 * ( y ) + 7x = -24
-4 * ( 11/6x + 6 ) + 7x = -24
( -44/6x - 24 ) + 7x = -24
-44/6x + 7x = -24 + 24
You can see immediately that ...x = 0
Just for fun of it ....
-44/6x + 42/6x = 24 - 24
(-44+42)/6x = 0
-2/6x = 0
-1/3x = 0
multiply left and right of the = sign by -3
3/3x = 0 * -3
x = 0
Step 3.
y = 11/6( x ) + 6. and substitute x = 0 gives:
y = 11/6( 0) + 6
y = 0 + 6
y = 6
You add 49,529 and 308
49,837
X-3/8=3/6
Add 3/8 to both sides, to leave the variable alone
X= 3/6-3/8
Use common denominators-8 (3/6 is 1/2)
X= 4/8-3/8
X=1/8
We just check on the graph and see that
the answer is x = -7 and x = 2